ACTUAL PROBLEMS OF STUDYING THE PHENOMENON OF CHIVALRY AT THE PRESENT STAGE - Pavel A. Gorbunov (Вестник Северо-Кавказского федерального университета, 2022)
This article details the problems of studying the relevance of chivalry. Particular attention is paid to the is- sues from the viewpoint of new theoretical and methodological approaches, in particular historical anthropology.